Implementation of Religious Character Education through the Friday Faith Program - Arsad, Muhammad; Musthofa, Musthofa (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research aims to discuss the implementation of religious character education through the Friday Faith program along with the supporting and inhibiting factors at SMA Negeri 1 Budong-Budong, West Sulawesi. The research method used in this research is a descriptive qualitative research method, while the data collection techniques used are observation, interviews and documentation. Data analysis in this research is by collecting data, reducing data, presenting data, and drawing conclusions or verification. The results of this research show that the implementation of religious character education at SMA Negeri 1 Budong-Budong is going well and is filled with several sessions such as the reading of prayers (tahlil or istighosah, reading juz 30 in groups, reading asmaul husna, and tausiyah. Because of this, several positive values emerged. Some of the supporting factors include the enthusiasm of teachers and students in participating in Friday Faith activities, adequate facilities, optimal time management, while the inhibiting factors are lack of care from parents, the community environment, excessive use of smartphones, and the students' own backgrounds.